Antimicrobial Efficacy of Biodegradable Films and Coatings on Beef - Mohd Shahid, Nadiatul Syima Bt (Curtin University, 2016)
Chilled fresh and processed meat product surfaces can be contaminated with pathogenic and spoilage bacteria. These bacteria can impact the safety and shelf life of these products. New approaches to effectively control bacteria on meat are constantly being sort. Antimicrobial films and coating produced from the plant protein kafirin, and containing essential oils or nisin, were shown to have potential to control these bacteria, improve the safety and reduce the spoilage of meat products.